N-(4-Chlorophenyl)-1,1,1-trifluoro-N-(trifluoromethylsulfonyl)methanesul fonamide - Boechat, N.; Lages, A.S.; Kover, W.B.; Tiekink, E.R.T.; Wardell, J.L.; Wardell, S.M.S.V. (International Union of Crystallography, 2010)
The title molecule, also called 4-chloro-N,N-bis(trifluoromethanesulfonyl)aniline, C8H4ClF6NO4S2, has non-crystallographic twofold symmetry with the pseudo-axis aligned along the Cl-C center dot center dot center dot C-N backbone of the molecule: the SO2CF3 residues lie to either side of the benzene ring. In the crystal, the presence of C-H center dot center dot center dot O contacts lead to the formation of a sequence of 12-membered {center dot center dot center dot HC2NSO}(2) synthons within a supramolecular chain aligned along [101].